2021
DOI: 10.1088/1742-6596/1743/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

A new synergistic approach for crop discrimination in a semi-arid region using Sentinel-2 time series and the multiple combination of machine learning classifiers

Abstract: Accurate monitoring of agricultural lands and crop types is a crucial tool for sustainable food production. Therefore, to provide reliable and updated crop maps, the improvement of satellite image classification approaches is essential. In this context, machine learning algorithms present a potential tool for efficient and effective classification of remotely sensed data. The main strengths of machine learning algorithms are the capacity to handle data of high dimensionality, and mapping classes characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…en, this pixel is affected to a class having the highest probability of pixel belonging. MLC is a one of the most commonly used supervised classification methods in remote sensing to derive land use/cover maps [3,[42][43][44]. SVM Classifier.…”
Section: Machine Learning-based Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…en, this pixel is affected to a class having the highest probability of pixel belonging. MLC is a one of the most commonly used supervised classification methods in remote sensing to derive land use/cover maps [3,[42][43][44]. SVM Classifier.…”
Section: Machine Learning-based Classificationmentioning
confidence: 99%
“…e support vector machine (SVM) is one of the most useful machine learning algorithms. It is based on statistical learning theory and has been extensively exploited in remote sensing for LC/LU mapping and crop classification [44].…”
Section: Machine Learning-based Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that RS approaches can be used to produce reliable crop area estimates and crop type classification [39,[70][71][72]. In the ASA region of Arizona, nine major crop types were able to be classified using a RS approach with an overall accuracy of >85% [41].…”
Section: Identifying and Estimating Crop Areamentioning
confidence: 99%
“…However, high-resolution satellite data such as Landsat and Sentinel images are available and provide huge amounts of data regularly on large areas in short time and remotely. Satellite image-based land cover land use mapping, generally, still have some challenges despite the improvement of spatial and temporal resolution [26][27][28][29]. Particularly, forest tree species discrimination can face the presence of similar classes in the study area and/or the presence of several features within the same pixel, contributing to spectral confusion between different forest over types [30,31].…”
Section: Introductionmentioning
confidence: 99%